Sentiments d’injustice et théorie du complot. Représentations d’adolescents migrants et issus des migrations africaines (Maroc et Afrique subsaharienne) dans des quartiers précaires de Bruxelles - Jacinthe Mazzocchetti (Brussels Studies)
Following a field survey in neighbourhoods and schools in the poor area of Brussels among adolescents from an African migrant background (Morocco and sub-Saharan Africa), this article examines young people’s attempts to rationalise the discrimination and injustice they experience. As well as their direct effects in terms of social success in particular, institutional discrimination and violence have repercussions on representations of oneself and of the world. The accumulation of experiences of discrimination and xenophobia – in particular when carried out by institutions – is interpreted by certain adolescents as being a conspiracy resulting in a reinforcement of “them/us” stratifications and logics of mistrust.